Learning practices and challenges among Thai public, state enterprise and private sectors in delivering public values - Punnitamai, Werawat (2018)
Creating learning values in organizations with the aim of improving service delivery is a must in today's time. This study examines three dimensions of learning organization practices. The focus is on the Thailand's public enterprise sector, public sector and private sector. The study consists of three major learning organization dimensions: (1) promoting a supportive learning environment within organizations; (2) establishing concrete learning process; and (3) positioning a leadership that supports learning. A survey was done among individuals working in state enterprises and the private and public sectors in order to determine the effects of the role played by the above-mentioned sectors' nature of business or operations, its size and its interaction effects in the success of establishing a learning organization.
An organizational-level Multivariate Analysis of Covariance (MANCOVA) reveals that private organizations exhibit significantly more activities across three learning organization dimensions; psychological safety, education and training and knowledge transfer. employees in private organizations-especially in the finance and banking sector-perceive a higher level of psychological safety under a supportive learning climate and environment. Additionally, the natures of business organizations-production, construction and real state-exhibit a higher level of concrete learning practices and reflection on work processes. Furthermore, the number of employees affects the process of analytical thinking within organization sectors, the nature of business, and number of employees on the sub-dimension, psychological safety in the workplace.
Finally, this study discusses the challenges of psychological safety and leadership roles on creating learning practices, then provides recommendations on leading roles in establishing a psychological safety environment as a fundamental ground for creating the learning organization.
Keywords: Organizational learning; Public value; Public administration -- Thailand -- Moral and ethical aspects; Learning Management Sytem (Thailand)